Strategus aloeus (Coleoptera: Scarabaeidae) damage in two agave species and its management based on entomopathogenic fungi in oil suspensions - Aquino-Bolaños, Teodulfo; Aquino-López, Tlacaelel; Ruiz-Vega, Jaime; Bautista-Cruz, Angélica (Revista Colombiana de Entomología, 2024)
Due to its agroecological characteristics, more than 24 species of agave have been developed and cultivated in the state of Oaxaca, Mexico, which have been fully exploited for the production of mezcal, an activity of economic importance. This crop is affected by the incidence of Strategus aloeus (Coleoptera: Scarabaeidae), an insect that causes damage and losses of economic importance to agave plants less than 3 years of age, for its control systemic insecticides are used; however, due to the habits of the insect, biological control is an alternative for its management. In this study, losses and damage caused by adults of S. aloeus on Agave potatorum Zucc. and A. angustifolia Haw. were determined from field observations. In the laboratory, two entomopathogenic fungi, Beauveria bassiana and Metarhizium robertsii (formerly known as M. anisopliae), were evaluated at a concentration of 1X107 conidia/insect in vegetable oil emulsions (Persea americana, Ricinus communis, and Prunus dulcis) at two concentrations of 20 % and 40 %. The damage found for A. potatorum with a sample size of 85 plants evaluated was 79.90 %. For A. angustifolia, with the same number of plants, 65.86 % damage was found. The losses found in 85 plants of A. angustifolia with damage grades 4 and 5 were 1 794.9 and 2 227.5 g/plant and for A. potatorum with damage grades 4 and 5 were 1 631.9 and 2 119.7 g/plant. In the laboratory, 48 hours were needed for 10 0% effectiveness on S. aloeus adults with the treatments B. bassiana + P. americana 40 % and B. bassiana + P. dulcis 40 %.